Perovskite fiber-shaped optoelectronic devices for wearable applications. Issue 18 (28th April 2022) - Balilonda, Andrew; Li, Ziqi; Fu, Yuequn; Zabihi, Fatemeh; Yang, Shengyuan; Huang, Xinxin; Tao, Xiaoming; Chen, Wei
Abstract : This review focuses on the progress in fiber-shaped self-powered perovskite devices, the benefits of the fiber geometry in optoelectronics, the challenges facing perovskites, and the possible recycling pathways of the material. Abstract : The miniaturization of electronic devices and rapid development of fabrication technologies have promoted wearable electronics. However, the power requirement imposes a considerable energy consumption burden on the main grid. Accordingly, fiber-shaped optoelectronic devices provide a solution to self-power devices and a direct route to achieve green, sustainable, and flexible photovoltaic platforms. Moreover, due to the numerous benefits associated with the fiber geometry, such as high flexibility, ease of integration with other devices, light weight and conformability to the human body and other structural shapes, the need to develop highly efficient and stable optoelectronic fiber-shaped devices for applications such as solar energy harvesting, communication, and advanced sensing is increasing. A photoactive layer is a vital component in any optoelectronic device. Perovskite, a new photoactive material with superb energy conversion efficiency and solution processability, offers the opportunity to achieve low-cost and high-performance fiber-shaped optoelectronic devices. Herein, we summarize the recent approaches and the possible future directions in the field of perovskite fiber-shaped optoelectronic devices (solar cells, solar-batteries, photodetectors, light-emitting devices, solar-capacitors, and solar-muscles/actuators). The technical benefits of the fiber geometry accompanied by a discussion on the possible layer deposition methods on fiber substrates are also presented. Furthermore, the challenges associated with perovskite materials, the proposed solutions, and the possible recycling pathways for perovskite-powered devices are discussed.